Social interaction in game communities and second language learning - Ang, Chee Siang; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2005)
This paper examines models of social interaction in computer game communities that could be harnessed to support learning and especially the learning of a second language. We demonstrate that learning is not only embedded in the game, but also in the in-game and out-of-game community that emerges from the game.
Keywords: Computer games; Game community; Social interaction; Second language learning